Hi Solving leaving the answer in term of e or ln (5^3+x) = (20^x-3) ln 5 (3 + x) = ln 20 (x - 3) 3 ln5 + x ln5 = x ln20 - 3 ln20 3 ln5 + 3 ln20 = x(ln20 - ln5) can it be simplified more?
Follow Math Help Forum on Facebook and Google+
ln(20)=ln(4*5)=ln(4)+ln(5)=ln(2^2)+ln(5)=2ln2+ln(5 )
Originally Posted by danielh9103 Hi Solving leaving the answer in term of e or ln (5^3+x) = (20^x-3) ln 5 (3 + x) = ln 20 (x - 3) 3 ln5 + x ln5 = x ln20 - 3 ln20 3 ln5 + 3 ln20 = x(ln20 - ln5) can it be simplified more? You should start learning LaTeX - this is hard to read. I assume that you mean So, This is what you wrote so far. But you're not done yet...
Last edited by eumyang; Jul 29th 2010 at 07:34 AM. Reason: OP stated that answer needs to be in terms of e or ln
View Tag Cloud